3D cell printing of in vitro stabilized skin model and in vivo pre-vascularized skin patch using tissue-specific extracellular matrix bioink: A step towards advanced skin tissue engineering. (June 2018) - Kim, Byoung Soo; Kwon, Yang Woo; Kong, Jeong-Sik; Park, Gyu Tae; Gao, Ge; Han, Wonil; Kim, Moon-Bum; Lee, Hyungseok; Kim, Jae Ho; Cho, Dong-Woo
Abstract: 3D cell-printing technique has been under spotlight as an appealing biofabrication platform due to its ability to precisely pattern living cells in pre-defined spatial locations. In skin tissue engineering, a major remaining challenge is to seek for a suitable source of bioink capable of supporting and stimulating printed cells for tissue development. However, current bioinks for skin printing rely on homogeneous biomaterials, which has several shortcomings such as insufficient mechanical properties and recapitulation of microenvironment. In this study, we investigated the capability of skin-derived extracellular matrix (S-dECM) bioink for 3D cell printing-based skin tissue engineering. S-dECM was for the first time formulated as a printable material and retained the major ECM compositions of skin as well as favorable growth factors and cytokines. This bioink was used to print a full thickness 3D human skin model. The matured 3D cell-printed skin tissue using S-dECM bioink was stabilized with minimal shrinkage, whereas the collagen-based skin tissue was significantly contracted during in vitro tissue culture. This physical stabilization and the tissue-specific microenvironment from our bioink improved epidermal organization, dermal ECM secretion, and barrier function. We further used this bioink to print 3D pre-vascularized skin patch able to promote in vivo wound healing. In vivo results revealed that endothelial progenitor cells (EPCs)-laden 3D-printed skin patch together with adipose-derived stem cells (ASCs) accelerates wound closure, re-epithelization, and neovascularization as well as blood flow. We envision that the results of this paper can provide an insightful step towards the next generation source for bioink manufacturing.